Design and fabrication of hydraulic crane for preschool education / Alnizar - Alnizar, Alnizar (2022)
Hydraulic system is a simple system yet useful in our daily life. Hydraulic is commonly used in construction and automotive industry. However, lack of exposure and study about hydraulic make some people did not realize the advantage and benefit using this system. Therefore, this project conducted to make a hydraulic crane machine that suitable to use in preschool education level. Several methods are used to fabricate this product. For example, cutting, grinding, and drilling. This project is going to use wood or cardboard because this is the suitable material for children to operate. The product will be able to provide a comfortable environment to study about heavy machine. Expecting this will increase the awareness about advantages of using hydraulic and add a new knowledge to kindergarten kids from a young age without bringing them to an uncomfortable environment to study about heavy machine. In conclusion this study is to design and fabricated a functional mini machine which can be used as learning material.